Expectations of the Generation NeXt in Higher Education: Learning Engagement Approaches in Information Sciences Subjects - Gütl, C.; Chang, Vanessa; Cheong, C.; Cheong, C.; Nau, S; Cheong, F.; Cheong, F.; Pirker, J.; Pirker, J. (2015 IEEE, 2015)
New learning tools, media and technologies, such as computer games, mobile devices, web services and social media, have improved the way learners learn and interact to acquire knowledge and skills. Recent generation of students entering universities known as Generation NeXT are digital natives who expect information to be available at any time and from anywhere. It is also well-known that this new generation of learners takes information in smaller portions and has shorter attention span. Educators are left to brace with the challenge of ensuring that they are able to use digital media and technologies when designing learning materials. In addition, educators must also work on capturing the attention of the new generation of learners. As such, educators are applying newer pedagogies to engage and motivate students with learning activities and interactions. This paper focuses specifically on learning engagement approaches in information sciences subjects. Three showcases from three universities in two countries with a variety of learning activities and engagements are illustrated. A generalized learning engagement model comprising of six active learning elements of (1) learning resources, (2) learning activities, (3) personalized learning, (4) active communication and collaboration, (5) feedback and reflection learning, and (6) student support is described. The results from the 3 cases showed that most of the active learning elements were addressed in the courses. The students found the learning activities within the courses were carefully orchestrated and thus gave them positive learning experiences.